KNOWLEDGE LOCAL GOVERNANCE SEBAGAI UPAYA MENINGKATKAN DAYA SAING DAERAH - M.Si, Dra. Agustin Rina Herawati, (Jurnal Desentralisasi, 2010)
Implementation of local autonomy is perceived as a mean in enhancing local economy if it is supported by effective local regulation. Major challenge of localautonomy empowerment is the understanding of local competitiveness potential. Accurate and comprehensive understanding of local competitiveness potential ofa region is beneficial to local government in formulating effective policy in order to create conducive environment for doing business in the region. I other words,local government must have knowledge in order to enhance local competitiveness